Cyclophotocoagulation in Neovascular Glaucoma with Near-Total Synechial Angle Closure - Jessie Wang; Lindsay Y. Chun; Mary Qiu (Case Reports in Ophthalmological Medicine)
Objective. To describe a single surgeon’s experience utilizing prompt primary slow-burn transscleral cyclophotocoagulation (CPC) with prior or concurrent anti-VEGF and subsequent aqueous shunt as needed in NVG eyes with near-total synechial angle closure at presentation. Methods. Retrospective chart review of all NVG patients with uncontrolled IOP, active anterior segment NV, near-total synechial angle closure, and no contraindications to prompt anti-VEGF who received CPC within 3 days of presentation with at least 6 months of follow-up. Results. Eight patients with mean age 60.6 years were included. Underlying etiologies were CRVO (N=3), PDR (N=2), CRAO (N=1), BRVO (N=1), and chronic RD (N=1). All eyes underwent CPC with intravitreal anti-VEGF within 3 days of presentation. Five patients did not require subsequent aqueous shunts through a mean follow-up of 15 months; most recent visual acuities ranged from 20/40 to LP, and IOPs ranged from 5 to 11 mmHg on 0 to 3 IOP-lowering medications. Three patients who required subsequent tubes had complete regression of active anterior segment NV at the time of surgery. Most recent visual acuities ranged from 20/100 to 20/125, and IOPs ranged from 8 to 14 mmHg on 0 meds at a mean follow-up of 10 months. No eyes developed uncontrolled inflammation, sympathetic ophthalmia, or phthisis. Conclusion. Prompt primary slow-burn CPC with prior or concurrent anti-VEGF may be an effective strategy to immediately lower IOP in acute NVG eyes with active anterior segment NV and near-total synechial angle closure. If IOP becomes uncontrolled later, an aqueous shunt can be implanted in a controlled setting after active anterior segment NV has regressed.